The Effect of Project-Based Learning Model Using Youtube Social Media on Students' Emotional Intelligence - Rasito, Rasito; Suyitno, Y; Purwandari, Ristiana Dyah; Fah, Lay Yoon (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to determine the effect of a project-based learning model using social media YouTube on students' emotional intelligence in learning entrepreneurial themes. This research is a pre-experimental study with a one group pre-test and post-test design. Respondents in this study were 30 grade VI students of SDN 3 Rawaheng. The data obtained is in the form of normalized g-score. The analysis was performed using the T-test one group pre-test and post test. Based on the results of the analysis, there was an increase in the mean value of each aspect of emotional intelligence. The average score of students' intelligence increased from 68.00 to 82.29 with an N-gain of 0.65 and sig * 0.00 <0.05